INOVASI PEMETAAN NAGARI DENGAN TEKNOLOGI GOOGLE EARTH DI PASIR TALANG SELATAN KECAMATAN SUNGAI PAGU KABUPATEN SOLOK SELATAN - Danny Hidayat; Fauziah Putri Khuzaimah; Rafly Putra Pratama (LPPM Universitas Andalas, 2023)
Nagari Pasir Talang Selatan does not yet have a complete village map as a support for administrative office completeness and village data. A village map is an essential aspect that should be possessed by each Nagari. Therefore, the government of Nagari Pasir Talang Selatan needs to have a village map to assist in village governance. The village map greatly aids in supporting the planning of a region's development and serves as a basis for renewing detailed plans in urban spatial planning. Hence, a work program is needed for the creation of this village map. The objective of this activity discusses the utilization of Google Earth as an effective tool in creating administrative maps for Nagari Pasir Talang Selatan. This can significantly contribute to providing accurate geospatial data and administrative information for the Nagari. The activity was conducted in Nagari Pasir Talang Selatan, Sungai Pagu District, South Solok Regency, West Sumatra Province. The implementation method in creating the village map starts with location surveys, determining coordinate points, and drawing map lines that match those displayed on the Google Earth map. The use of Google Earth technology can yield accurate and up-to-date administrative maps. The outcome of this activity is the successful completion of creating the village map, which can facilitate ease of access for those needing information about the Nagari and aid the village government in monitoring land use within the area. This program represents a positive step in the development of Nagari Pasir Talang Selatan and brings significant benefits to the community and local government. To enhance the effectiveness of this program, there is a need for the development and updating of the village map based on the area's developments.